2017
DOI: 10.11648/j.ijnfs.20170602.18
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soaking and Germination on the Iron, Phytate and Phenolic Contents of Maize Used for Complementary Feeding in Rural Tanzania

Abstract: Abstract:Introduction: In developing countries including Tanzania, complementary foods fed to children are often carbohydrate-based and lack sufficient protein, energy, vitamins and micronutrients. Evidence suggests that the iron contained in foods such as cereals is not fully absorbed and will collect in the colon with the possibility of free radical generation and intestinal inflammation. Plant-based complementary foods have been reported to contain high levels of phytate and phenolic compounds, which impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In germinated green gram, Bengal gram, and horse gram, the Fe content increased 75.47, 34.24, and 21.21%, respectively, compared to ungerminated kernels. Mihafu et al reported an increase of 50% of Fe in germinated maize after 72 h . Also, the increase of Mg content in germinated kernels, such as barnyard and Kodo millets, of 11.5 and 11.2%, respectively, has been reported .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In germinated green gram, Bengal gram, and horse gram, the Fe content increased 75.47, 34.24, and 21.21%, respectively, compared to ungerminated kernels. Mihafu et al reported an increase of 50% of Fe in germinated maize after 72 h . Also, the increase of Mg content in germinated kernels, such as barnyard and Kodo millets, of 11.5 and 11.2%, respectively, has been reported .…”
Section: Resultsmentioning
confidence: 95%
“…16 In germinated green gram, Bengal gram, and horse gram, the Fe content increased 75.47, 34.24, and 21.21%, respectively, compared to ungerminated kernels. Mihafu et al reported an increase of 50% of Fe in germinated maize after 72 h. 17 Also, the increase of Mg content in germinated kernels, such as barnyard and Kodo millets, of 11.5 and 11.2%, respectively, has been reported. 18 Chinma et al reported that dry matter losses normally occur during germination, mainly attributed to degradation of carbohydrates and lipids, and that these losses increase the concentrations of minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested addition of animal products, the use of commercial infant formulas (Idris et al, 2019) as well as micronutrient powders (Solomon et al, 2017) to improve iron status of infants and young children in developing countries. In order to increase iron content and reduce anti-nutrients such as phytates, some studies suggested soaking and germination of cereals and legumes prior to processing (Mihafu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%